Study on Dynamics of Wind Turbine Gearbox with Crack Fault under Random Wind Load - Jinwen Wang; Xiayue Ma; Zihao Liu; Xiaolu Leng; Shijing Wu (Jixie chuandong)
Crack fault will affect the time-varying meshing stiffness of the gear，and cause the vibration response of gear transmission system. Taking the wind turbine gearbox as the research object，considering the misalignment of gear root circle and base circle，an improved energy method is used to calculate the time-varying meshing stiffness of each gear pair. Based the improved method，the influence of sun gear crack on meshing stiffness is calculated and analyzed. Wind turbine gearbox operates in a natural wind load environment，and is excited by time-varying speed and torque. The translation-torsional-axial coupling model of wind turbine gearbox is established by using the lumped parameter method and considering backlash，time-varying meshing stiffness，meshing error parameter. The Runge-Kutta method is adopted to get the system dynamics response，and the order analysis of the response is carried out. The influence of the sun gear crack fault on the vibration response of wind turbine geatbox is obtained，and the fault failure mechanism of sun gear crack fault of wind turbine gearbox is studied. The conclusions provide theoretical reference for online monitoring and fault diagnosis of wind turbine gearbox.